Environmental flow assessment : methods and applications - Williams, John G., 1941-; Moyle, Peter B.; Webb, J. Angus, 1971-; Kondolf, G. Mathias (John Wiley & Sons, Inc., 2019)
4.1 Introduction; 4.2 Structure of stream ecosystems; 4.2.1 Across-channel gradients; 4.2.2 Upstream-downstream gradient; 4.3 Adaptations of stream organisms; 4.3.1 Morphological adaptations; 4.3.2 Physiological adaptations; 4.3.3 Behavioral adaptations; 4.4 Adapting to extreme flows; 4.5 Synthesis; 4.6 Environmental flows and fish assemblages; 4.7 Conclusions; Chapter 5 Tools for environmental flow assessment; Summary; 5.1 Introduction; 5.2 Descriptive tools; 5.2.1 Graphical tools and images; 5.2.2 Stream classifications; 5.2.3 Habitat classifications; 5.2.4 Species classifications
Keywords: Stream measurements.; Stream ecology.; Environmental impact analysis.; Environmental impact statements.; elektronické knihy; electronic books